2014
DOI: 10.1186/2251-6581-13-69
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant DNA methylation patterns in diabetic nephropathy

Abstract: BackgroundThe aim of this study was to evaluate whether global levels of DNA methylation status were associated with albuminuria and progression of diabetic nephropathy in a case-control study of 123 patients with type 2 diabetes- 53 patients with albuminuria and 70 patients without albuminuria.MethodsThe 5-methyl cytosine content was assessed by reverse phase high pressure liquid chromatography (RP-HPLC) of peripheral blood mononuclear cells to determine individual global DNA methylation status in two groups.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(37 citation statements)
references
References 55 publications
0
36
1
Order By: Relevance
“…The inclusion and exclusion criteria, retinopathy and nephropathy diagnosis criteria of the study population have been described previously [2123]. …”
Section: Methodsmentioning
confidence: 99%
“…The inclusion and exclusion criteria, retinopathy and nephropathy diagnosis criteria of the study population have been described previously [2123]. …”
Section: Methodsmentioning
confidence: 99%
“…In a separate study, DNA methylation profiling with the Infinium 27K bead array from samples of whole blood was used to identify 19 prospective CpG sites associated with risk of DN in T1DM compared to those without nephropathy . Additional studies using various DNA methylation assays and DNA collected from peripheral blood samples or saliva identified specific DNA methylation profiles for diabetic patients with and without nephropathy . Most of these studies proposed using DNA methylation profiles as biomarkers to help predict disease status and progression and did not report associated gene expression data.…”
Section: Diabetic Nephropathy and Dna Methylationmentioning
confidence: 99%
“…In animal models, epigenetic silencing due to increased promoter DNA methylation has been linked to islet dysfunction and development of diabetes [69,70]. In a casecontrolled study of 168 patients with type 2 DM, the global DNA methylation status was shown to be associated with DR. Additionally, the DNA methylation status exhibited a strong correlation with the progression of DR [71,72]. Apart from the increased activity of Dnmts in the retina and its capillary cells [73], histone-modifying machinery is also affected in diabetes.…”
Section: The Role Of Epigenetics In the Pathogenesis Of Diabetic Retimentioning
confidence: 99%